Honeypot-based intrusion detection system: A performance analysis (Texas Journal of Multidisciplinary Studies, 2022)
Attacks on the internet keep on increasing and it causes harm to our security system. In order to minimize this threat, it is necessary to have a security system that has the ability to detect zero-day attacks and block them. “Honeypot is the proactive defense technology, in which resources placed in a network with the aim to observe and capture new attacks”. This paper proposes a honeypot-based model for intrusion detection system (IDS) to obtain the best useful data about the attacker. The ability and the limitations of Honeypots were tested and aspects of it that need to be improved were identified. In the future, we aim to use this trend for early prevention so that pre-emptive action is taken before any unexpected harm to our security system.